2013
DOI: 10.1183/09031936.00054613
|View full text |Cite
|
Sign up to set email alerts
|

It's the adherence, stupid (that determines asthma control in preschool children)!

Abstract: Although guideline-based asthma care and adherence to inhaled corticosteroids are predictors of asthma control, the role of adherence in maintaining long-term asthma control is largely unknown. This study was designed to explore the relationship between adherence to inhaled corticosteroids and long-term asthma control in young children with asthma.In this observational study, 81 2-6-year-old asthmatic children, using inhaled corticosteroids, closely followed-up in a programme with extensive self-management tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
8
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 24 publications
7
64
8
11
Order By: Relevance
“…Atopy did not predict the response to ICS in this meta-analysis [22]. A recent report showed that the degree of asthma control achieved in 2-6 year old children was most strongly determined by their adherence to ICS treatment [23]. The lack of data on the symptom pattern in this study does not allow a firm conclusion whether this applies to both EVW and MTW.…”
Section: Indications For and Choice Of Controller Therapycontrasting
confidence: 47%
“…Atopy did not predict the response to ICS in this meta-analysis [22]. A recent report showed that the degree of asthma control achieved in 2-6 year old children was most strongly determined by their adherence to ICS treatment [23]. The lack of data on the symptom pattern in this study does not allow a firm conclusion whether this applies to both EVW and MTW.…”
Section: Indications For and Choice Of Controller Therapycontrasting
confidence: 47%
“…Так, в наблюдениях, в которых следование рекомендациям определялось с помощью электронных устройств, средний уровень приверженности составил 30-70% к общему количеству назначенных доз ИГКС [18]. В других работах отмечено, что уже 75%-е соблю-дение рекомендаций по использованию ИГКС дает у взрослых и детей полный или частичный контроль над астмой [18,19]. Таким образом, низкая приверженность назначенному режиму применения ИГКС значительно снижала эффективность лечения, приводила к некон-тролируемой БА и увеличивала расходы бюджетных средств [20].…”
Section: приверженность лечениюunclassified
“…Несоблюдение назначений -рас-пространенная причина персистирования симптомов у данной группы пациентов [5,10]. Исследования при-верженности и контроля над легкой или среднетяжелой астмой показали, что главной причиной хрипов, одыш-ки, ночного кашля, персистирующих слабовыраженных симптомов, которые могут провоцироваться физической нагрузкой, также является несоблюдение назначенных рекомендаций [14,19].…”
Section: приверженность лечениюunclassified
“…They found a surprisingly high median adherence rate of 87% (interquartile range 61-94%). All studied children were taking part in an extensive self-management training programme [32]. It has been recommended that drug administrations should be reduced as a way of increasing adherence.…”
Section: Paediatric Asthma and Allergymentioning
confidence: 99%